Literature of the Lost Generation and the Generation of the Returned: Comparative Aspect of Analysis (Proceedings of Southern Federal University. Philology, 2020)
The article proposes approaches to the study of the works of authors representing the literature of the lost generation and the generation who returned to practical training in foreign literature at the university. The indicated literary phenomena are considered in the context of the eras of Modern and Postmodern.Key words: First World War, World War II, literature of the lost generation, literature of the generation of returnees, the image of war, the problem of «manwar», a hero, a «little» man.DOI 10.18522/1995-0640-2020-2-190-197